Cochlear implantation in a child with subtelomeric 1q deletion syndrome and Dandy-Walker malformation - Cevizci, Raşit; Bezgin Üstün, Selin; Dizdar Turan, Handan; Yılmaz, Oğuz; Kersin, Burak; Bayazıt, Yıldırım Ahmet (Elsevier Ireland Ltd, 2016)
Subtelomeric 1q deletion syndrome is a rare disorder characterized by severe mental and growth retardation, microcephaly, distinct facial features and corpus callosum abnormalities. Senserineural hearing loss is not common in this syndrome. We report a 2-year-old boy with subtelomeric 1q deletion syndrome presented with typical craniofacial abnormalities and bilateral senserineural hearing loss. Imaging revealed corpus callosum hypogenesis and Dandy-Walker malformation. Cochlear implantation was successfully undertaken using a transmastoid facial recess aproach. After 12-months post-implantation, good audiological outcomes were obtained. Cochlear implantation can be considered for hearing rehabilitation in patients with subtelomeric 1q deletion syndrome and Dandy-Walker malformation.
WOS: 000436437100004
Keywords: 1q Subtelomeric Deletion; Cochlear Implant; Dandy-Walker Malformation